Trainee colonoscopy quality is influenced by the independent and unobserved performance characteristics of supervising physicians - Mahadev, Srihari; Jin, Zhezhen; Lebwohl, Benjamin; Rosenberg, Richard M.; Garcia-Carrasquillo, Reuben J.; Ramirez, Ivonne; Freedberg, Daniel E. (Endoscopy International Open, 2019)
Background Endoscopy training remains an apprenticeship, and the characteristics that facilitate transfer of high quality procedural skills from role models to trainees are unknown. We sought to determine whether unobserved supervisor performance influences the quality of colonoscopy performed by trainees, by studying how supervisors perform alone and how trainees perform while under those same supervisors.Methods This was a retrospective cross-sectional study conducted among ambulatory adults ≥ 50 years old who underwent colonoscopy for cancer screening or polyp surveillance from 2006 to 2015 at one academic medical center. The primary exposures were the colonoscopy withdrawal time (WT) and adenoma detection rate (ADR) of supervisors while performing colonoscopies alone. The primary outcomes were the WT and ADR of trainees performing colonoscopies under supervision.Results Data were included from 22 attending gastroenterologist supervisors, 56 gastroenterology fellow trainees, and 2777 adults undergoing 3094 colonoscopy procedures. Among all supervised colonoscopies, mean trainee WT was 12.7 minutes (SD 4.9) and trainee ADR was 33.5 %. The trainee WT was 0.42 minutes longer (standard error = 0.16, P = 0.01) per minute increase in supervisor WT. Similarly, trainee ADR was higher under a high ADR supervisor, and the odds ratio of high compared to low supervisor ADR category was 1.28 (95 %CI 1.01 – 1.62, P = 0.04) after adjusting for other factors.Conclusions The unobserved performance characteristics of supervising endoscopists may influence the quality of colonoscopy performed by trainees.